Original paperLong-term prognostic value of admission hemoglobin A1c (HbA1c) level in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention - Pusuroglu, Hamdi; Akgul, Ozgur; Cakmak, Huseyin Altug; Erturk, Mehmet; Surgit, Ozgur; Celik, Omer; Ozturk, Derya; Uzun, Fatih; Akkaya, Emre; YIldIrIm, AydIn (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : Many studies have reported the diagnostic and prognostic value of haemoglobin A 1c (HbA 1c ) levels in patients with acute coronary syndrome. However, the short- and long-term prognostic value of HbA 1c level in patients with ST elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI) is controversial. Aim: To investigate whether admission HbA 1c level has a prognostic value for in-hospital, short-, and long-term cardiovascular (CV) mortality and major adverse cardiovascular events in patients with STEMI undergoing primary PCI. Material and methods : This prospective study included 443 consecutive patients with STEMI who underwent primary PCI between September 2010 and July 2012. The patients were divided into three groups based on admission HbA 1c levels: group I  (HbA 1c ≤ 5.6%), group II (HbA 1c 5.7–6.4%), and group III (HbA 1c ≥ 6.5%). The in-hospital, 1-month, and 1-year CV events of all 3 patient groups were followed up. Results: A significant association was found between HbA 1c level and 1-year primary clinical outcomes, including CV mortality, non-fatal reinfarction, and stroke (p = 0.037). In addition, age, Killip class > 1, and left ventricular ejection fraction were found to be independent predictors of long-term CV mortality in multivariate analysis (hazard ratios (95% confidence interval) 1.081 (1.020–1.146), 4.182 (1.171–14.935), and 0.832 (0.752–0.920); p = 0.009, p = 0.028, and p < 0.001, respectively). Conclusions : In this study, we demonstrated that increased admission HbA 1c levels were associated with higher rates of major adverse CV events, including mortality, non-fatal reinfarction, and stroke, in patients with STEMI who underwent primary PCI.